The Quantum Dynamics of Natural Distributed Oscillatory Systems - Gritsunov, A. V. (My University, 2016)
A statistical method for the quantization of natural electromagnetic (NEMOS) and electron-positron (NEPOS) oscillatory systems is discussed. The Wheeler-Feynman’s concept of “direct interparticle action” for the quantum radiation-absorption is generalized to the Coulomb interaction. The energy-momentum conservation is postulated as a fundamental law forbidding any objective their “uncertainty”. The spatial (spatio-temporal) localization of NEPOS wavepackets and the Heisenberg’s “uncertainty principle” are supposed to be a result of a permanent interaction of NEPOS and NEMOS, i.e., the stochastic exchange with random quanta of momentum (or energy-momentum) between ones. The absence of “zero-point oscillations” of the natural oscillatory systems is asserted. The new physical sense of De Broglie wavefunctions is illustrated with the simplest quantum systems “electrons in potential wells”.
Keywords: oscillatory system; second quantization; direct interparticle action; zero-point oscillation